The Health-Promoting Lifestyle Assessment Among Nursing Students In East Kalimantan (Association of Public Health Scholars based in Faculty of Public Health, Sriwijaya University, 2022)
Nurses as a health professional has a significant role in primary health services in nurturing, and also enabling the community to healthy behavior. Nurse students will become role models for healthy lifestyles and as leaders to enable people to live healthy lives, this is inversely proportional to the possibility of their unhealthy lifestyles since the study period. The purposes of study were to assess the level health-promoting lifestyle among student of nursing and identify the differences in such lifestyle based on socio-demography. A cross-sectional descriptive study was conducted on 326 of nursing students in East Kalimantan. The data has been collected by Health-Promoting Lifestyle Profile II (HPLP II) level (i.e., responsibility of health, spiritual, physical activities, interpersonal relationship, student nutrition, and their stress management). Data was taken by online self-administered questionnaire. Participants were recruited by convenience sampling. Descriptive and inferential statistics data analysis has been conducted. It was found that 76.4% were female, 37.7% were in second years study, as much as 58.9% of students from municipality areas. The mean score of 2.79 (good) of total HPLP II. The highest mean score was shown for interpersonal relationship by nurse students 3.25 (excellent) and the lowest was daily nutrition (2.43) and physical activity (2.47) as moderate level. Based on independence t-test analysis there were differences statistically in physical activity between gender (p-value <0.001), there is a difference statistically in health responsibility between student from municipality and regency (p-value = 0.010). In general, the HPLP indicators for nursing students are good, but improvement and promotion of healthy lifestyles is still needed. Further identification as strengthening to determine the cause of low nutrition and physical activity. Aspects that must be maintained are interpersonal relationships and spiritual growth.